مقومات توطن صناعة طحن الحبوب: مطحنة الدورة أنموذجا - خليفة، ستار جبار (جامعة بغداد - كلية التربية ابن رشد, 2023)
تعد صناعة طحن الحبوب من اقدم الصناعات واشهرها فقد عرفها الإنسان منذ زمن بعيد، إذ تم استعمال الحجر للطحن ثم استعمل الماء والهواء لإدارة الطواحين إلى أن تم استعمال المكائن والآلات المتمثلة بالسلندرات والسفترات التي تعمل بالطاقة الكهربائية، كما شهدت هذه الصناعة تطورا كبيرا في العراق على مر العصور التي مرت عليه لاسيما في النصف الثاني من القرن العشرين، نتيجة ازدياد أعداد السكان ولكونها تشكل الغذاء الأساسي للإنسان، إذ تم إقامة عدة مطاحن في بغداد وباقي محافظات أخرى، منها مطحنة الدورة التي تم تأسيسها عام 1979 التابعة للشركة العامة لتصنيع الحبوب، وتمر هذه الصناعة بعدة مراحل ابتداء من استلام المادة الخام (الحنطة) من السايلوات إلى أن يتم طحنها وتحويلها للطحين ليعبأ وينقل إلى الوكلاء ومن ثم يوزع على المواطنين، ولأهمية هذه الصناعة كان لابد من دراسة مقومتها الجغرافية ومعرفة مدى مساهمة تلك المقومات في توطنها، إذ أن هنالك عدة مقومات تشكل عامل أساسي في مدى نجاحها ومنها عامل المواقع ومدى توفر المياه والطاقة الكهربائية والوقود، وعامل النقل الذي يعد من العوامل المهمة التي تسهم في نجاحها كونها تستعمل مواد أولية كبيرة ورخيصة الثمن، فضلا عن السياسة الحكومية وتدخلات الدولة المباشرة وغير المباشرة فيها. The grain milling industry is one of the oldest and most famous industries. It has been known to man since a long time ago. Stone was used for grinding, and then water and air were used to run the mills until the machines and machines represented by cylinders and cylinders powered by electric power were used. This industry also witnessed a great development in Iraq over the years. The eras that passed by, especially in the second half of the twentieth century, as a result of the increase in population numbers and being the basic food for humans, several mills were established in Baghdad and the rest of the other provinces, including the Dora Mill, which was established in 1979 affiliated with the General Company for Grain Manufacturing, This industry goes through several stages, starting from receiving the raw material (wheat) from the silos until it is milled and converted into flour to be packed and transported to agents and then distributed to the citizens. There are several factors that constitute a key factor in the extent of its success, including the factor of locations, availability of water, electric power and fuel, and the transport factor, which is one of the important factors that contribute to its success as it uses large and cheap raw materials, as well as government policy and direct and indirect state interventions in it.
Keywords: صناعة الحبوب -- الصناعات الغذائية -- طحن الحبوب -- العراق